2018
DOI: 10.1007/s10535-018-0769-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis from stem thin cell layers of Dendrobium aqueum

Abstract: An efficient in vitro regeneration protocol through somatic embryogenesis was established from stem transverse thin cell layers (tTCLs) of Dendrobium aqueum Lindley, an imperiled orchid. This study outlines the induction and successive maturation stages of D. aqueum somatic embryos (SEs). The tTCLs (~ 0.5 mm thick) cultured on halfstrength Murashige and Skoog (MS) medium containing cytokinins and auxins, either individually or in combination, produced embryogenic callus (EC). Treatment with 0.5 mg dm -3 zeatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
0
29
0
3
Order By: Relevance
“…In Dendrobium aqueum, only the cytokinin 2iP [N-6-(2-isopentyl) adenine] at 1.5 mg L −1 proved it efficiency in production of PLBs (42.7 PLBs per explants) from callus, compared to other cytokinins BA, Kin and Zea, and cytokinin-like compound TDZ. These authors also observed that arginine at 25 mg L −1 increased direct somatic embryogenesis, instead of callus derived PLBs [137]. Meta-Topolins, a natural aromatic type of cytokinin, were also reported used in induction and regeneration of PLBs in D. nobile, which combined with 0.5 mg L −1 NAA resulted in best PLBs formation (92%) and shoots/explants (9.2) [139].…”
Section: Some News With Cymbidium Dendrobium and Othersmentioning
confidence: 86%
See 1 more Smart Citation
“…In Dendrobium aqueum, only the cytokinin 2iP [N-6-(2-isopentyl) adenine] at 1.5 mg L −1 proved it efficiency in production of PLBs (42.7 PLBs per explants) from callus, compared to other cytokinins BA, Kin and Zea, and cytokinin-like compound TDZ. These authors also observed that arginine at 25 mg L −1 increased direct somatic embryogenesis, instead of callus derived PLBs [137]. Meta-Topolins, a natural aromatic type of cytokinin, were also reported used in induction and regeneration of PLBs in D. nobile, which combined with 0.5 mg L −1 NAA resulted in best PLBs formation (92%) and shoots/explants (9.2) [139].…”
Section: Some News With Cymbidium Dendrobium and Othersmentioning
confidence: 86%
“…As example, the combination of cytokinin BA (5.0 mg L −1 ) and auxin NAA (2.5 mg L −1 ) were used to induce PLBs (20.55 PLB per primary protocorm) in Cymbidium mastersii protocorms [134]. Thin cell layers (TCL) from different types of tissues was a technique used to improve the production of PLBs in Cymbidium [135], Dendrobium [136,137], Oncidium [129], and Phalaenopsis [93].…”
Section: Some News With Cymbidium Dendrobium and Othersmentioning
confidence: 99%
“…In at least two cases, tTCLs served as the donor explants for genetic transformation experiments (Croom et al, 2016;Vaidya et al, 2016), and root-derived TCLs continue to serve as basic tools in assessing axillary root development in A. thaliana (Della Rovere et al, 2016;Fattorini et al, 2017Fattorini et al, , 2018. Except for three studies (Bose et al, 2017;Bhattacharyya et al, 2018;Parthibhan et al, 2018), none of the other new studies, similar to the vast majority of older studies on TCLs (Teixeira da Silva and Dobránszki, 2015), assessed the genetic stability relative to plants derived from the conventional culture, and such genetic testing needs to be implemented in future research on TCLs. Parthibhan et al (2018) used inter-simple sequence repeats (ISSR) to confirm the monomorphic nature of the resulting somatic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Except for three studies (Bose et al, 2017;Bhattacharyya et al, 2018;Parthibhan et al, 2018), none of the other new studies, similar to the vast majority of older studies on TCLs (Teixeira da Silva and Dobránszki, 2015), assessed the genetic stability relative to plants derived from the conventional culture, and such genetic testing needs to be implemented in future research on TCLs. Parthibhan et al (2018) used inter-simple sequence repeats (ISSR) to confirm the monomorphic nature of the resulting somatic embryos. Bose et al (2017) tested genetic fidelity by flow cytometry and intron splice junction (ISJ) markers, finding some polyploidy (5-11% 8C) in the leaves of the donor and acclimatized plants when the former was used, and 5-17% polymorphism in tissue cultured plants when five of the 15 ISJ primers were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation